Employing cross-layer assisted TCP algorithms to improve TCP performance with vertical handoffs. (6th November 2008) - Daniel, Laila; Kojo, Markku
In this paper we study the performance of TCP with a vertical handoff between access networks with widely varying link characteristics. TCP being an end-to-end protocol has performance problems as its behaviour depends on the end-to-end path properties which are likely to be affected by a vertical handoff. We propose a set of enhancements to the TCP sender algorithm that leverage on explicit cross-layer information regarding the changes in the access link delay and bandwidth. We carry out a systematic study to identify the problems of regular TCP and compare the performance of the regular TCP with the performance of the enhanced TCP algorithms in various handoff scenarios between access networks having different bandwidth and delay characteristics. Our experiments show that with cross-layer notifications TCP performance can be improved significantly in most vertical handoff scenarios.